2007
DOI: 10.1007/s10875-007-9147-2
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoiesis, Regulatory T Cells, and TCRVβ Expression in Thymoma With and Without Myasthenia Gravis, and Modulatory Effects of Steroid Therapy

Abstract: We analyzed thymocyte and thymic regulatory T cell (CD4SPCD25+Foxp3+cells, Treg) development in thymoma with and without myasthenia gravis (MG, MG-thymoma, non-MG-thymoma) and in MG-associated non-neoplastic thymus (MG-NNT). An increased number of immature CD4+CD8(-)CD3(-) thymocytes through the CD4+CD8+ to CD4+CD8(-) transition and an abnormal T cell receptor Vbeta (TCRVbeta) development through the CD4+CD8+ to CD4(-)CD8+ transition were seen both in MG-and non-MG-thymomas. Terminal thymopoiesis, i.e., CD45RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…A research with French MG patients has found a normal Treg number but a severe dysfunction in thymus tissues [10], whereas other studies have shown that the Treg was decreased in both peripheral blood and the thymus of MG patients [9,25], and the Foxp3 expression was dramatically down-regulated [26]. Herein, we stratified all the MG patients based upon the histological type of thymoma, and observed similar expressions of CD4 and CD25 in all types of thymoma with OMG, GMG, and Non-MG.…”
Section: Discussionmentioning
confidence: 95%
“…A research with French MG patients has found a normal Treg number but a severe dysfunction in thymus tissues [10], whereas other studies have shown that the Treg was decreased in both peripheral blood and the thymus of MG patients [9,25], and the Foxp3 expression was dramatically down-regulated [26]. Herein, we stratified all the MG patients based upon the histological type of thymoma, and observed similar expressions of CD4 and CD25 in all types of thymoma with OMG, GMG, and Non-MG.…”
Section: Discussionmentioning
confidence: 95%
“…11 patients have been thymectomized because of thymic hyperplasia or thymoma, while other 10 patients have no abnormality of thymus. Until the study, all of the patients have not received the treatment of corticosteroid and other immune depressant at least one year to prevent from their effects [4]. 20 healthy controls (HCs), 10 males and 10 females Thymic histology Disease duration 1 M 26 IV Thymic hyperplasia 3 years 2 F 53 IIB Thymoma 2 months 3 F 63 IIA -7 years 4 F 30 IIA -6 months 5 F 84 IIB -8 years 6 M 58 I -2 years 7 F 56 IV Thymoma 12 years 8 M 63 IIA -5 years 9 F 37 IIA Thymic hyperplasia 1 year 10 M 77 I -2 years 11 F 48 IIA Thymoma 8 years 12 M 66 I -5 …”
Section: Patientsmentioning
confidence: 99%
“…On the other hand, PIT-1-reactive CTLs plays an essential role in the development of the disease 13 . In MG, it has been speculated that the first alteration in intratumorous T cell thymopoiesis may involve the generation of muscle-specific CTLs, and the resulting muscle damage could lead to various autoimmune responses including a production of autoantibodies against AChR and intracellular antigens 32 . It is speculated that anti-PIT-1 antibody may be produced after the injury of PIT-1 expressing cells by CTL and the resulting exposure of the nuclear protein PIT-1.…”
Section: Discussionmentioning
confidence: 99%